TRACE ELEMENTS IN SUPERGENE PHOSPHORITES - Zanin Yu.N.; Zamirailova A.G. (My University, 2007)
Supergene phosphorites were analyzed for Sr, Ba, Zn, Cd, Sc, Cr, Ag, and V, i.e., elements incorporated in carbonate-apatite by isomorphic substitution. The phosphorites were subdivided into four groups: (1) phosphorites related to the weathering of sedimentary rocks, (2) phosphorites related to the weathering of endogenous rocks, (3) lacustrine coprolite phosphorites, and (4) phosphorites of ocean islands. In all the phosphorites groups, Sr, Zn, and Ba were the most abundant of the trace elements, whereas Cd, Ag, and Sc showed the lowest concentrations. Variations in trace element contents between supergene phosphorites of different genetic groups or within a single group can be explained by the different compositions of weathered rocks and geochemical environments of supergene phosphorite formation. At the same time, the contents of some trace elements are correlated with the structural type of phosphorite. In particular, phosphorite crusts or only their outer parts show elevated contents of chalcophile elements (Cd, Zn, and Ag), whereas massive phosphorites and inner parts of crusts are often enriched in such lithophile elements as Sc, V, and Cr. It was found that Cd, Zn, Ag, Sr, and Ba are positively correlated with CO2 but show negligible correlations with other constituents of carbonate-apatite.